Pengamatan Okultasi Beta Scorpio oleh Planit Jupiter - B. Hidajat (Institute for Research and Community Services (LPPM) ITB, 1972)
The occultation of the multiple star Beta Scorpio by Jupiter was observed visually and photographically with the 24